Analysis of Hg(II) Metal by Voltammetric Method Using a Carbon Electrode Modified with EDTA from Used Tire Waste - Sukoma, Sukoma; Alva, Sagir; Safitri, Eka; Julinawati, Julinawati; Mustanir, Mustanir; Fonna, Syafrizal; Ihsan, Muhammad; Dara, Fitri; Dayanti, Meri; Arifin, Ahmad Kamal; Suhud, Khairi (Universitas Gadjah Mada, 2024)
Development of a carbon electrode sensor from used tire waste via pyrolysis, modified with ethylenediaminetetraacetic acid (EDTA) for mercury detection using the cyclic voltammetry (CV) method. EDTA plays a role in metal complexation due to its strong response to mercury metal. The FTIR results of the carbon electrode and EDTA show a C–N bond at a wavenumber of 1,217.08 cm−1, indicating the presence of EDTA. The SEM results reveal a clear difference between the unmodified carbon electrode and the EDTA-modified carbon electrode. The calibration graph is linear, with an R2 value of 0.9961, a sensitivity of 0.3472, as well as LoD and LoQ values of 0.03 and 0.08 ppm, respectively. The correlation coefficient is less than 2%, and the %recovery is within the allowable error range. Mercury measurements in Sungai Mas water samples, Aceh Barat, using voltammetry and AAS, exceed the threshold set by Indonesian Government Regulation (PPRI) No. 22 of 2021. The t-test results for the two Hg measurement methods at a 5% significance level (α) show that tcalculated < ttable (0.083 < 2.571). This indicates no significant difference between the voltammetry and AAS methods for measuring Hg concentrations in water.